# Difference between revisions of "1960 AHSME Problems/Problem 22"

## Problem 22

The equality $(x+m)^2-(x+n)^2=(m-n)^2$, where $m$ and $n$ are unequal non-zero constants, is satisfied by $x=am+bn$, where:

$\textbf{(A)}\ a = 0, b \text{ } \text{has a unique non-zero value}\qquad \\ \textbf{(B)}\ a = 0, b \text{ } \text{has two non-zero values}\qquad \\ \textbf{(C)}\ b = 0, a \text{ } \text{has a unique non-zero value}\qquad \\ \textbf{(D)}\ b = 0, a \text{ } \text{has two non-zero values}\qquad \\ \textbf{(E)}\ a \text{ } \text{and} \text{ } b \text{ } \text{each have a unique non-zero value}$

## Solution

Expand binomials, combine like terms, and subtract terms from both sides. $$x^2 + 2xm + m^2 - x^2 - 2xn - n^2 = m^2 - 2mn + n^2$$ $$2xm + m^2 - 2xn - n^2 = m^2 - 2mn + n^2$$ $$2xm - 2xn - n^2 = -2mn + n^2$$ Get all the x-terms on one side and factor to solve for x. $$2xm - 2xn = -2mn + 2n^2$$ $$2x(m-n) = -2n(m-n)$$ Since $m \not= n$, both sides can be divided by $m-n$. $$x = -n$$ That means $a = 0$ and $b = -1$, so the answer is $\boxed{\textbf{(A)}}$.

 1960 AHSC (Problems • Answer Key • Resources) Preceded byProblem 21 Followed byProblem 23 1 • 2 • 3 • 4 • 5 • 6 • 7 • 8 • 9 • 10 • 11 • 12 • 13 • 14 • 15 • 16 • 17 • 18 • 19 • 20 • 21 • 22 • 23 • 24 • 25 • 26 • 27 • 28 • 29 • 30 • 31 • 32 • 33 • 34 • 35 • 36 • 37 • 38 • 39 • 40 All AHSME Problems and Solutions